Anneslea fragrans Wall. ameliorates ulcerative colitis via inhibiting NF-κB and MAPK activation and mediating intestinal barrier integrity. (5th October 2021) - Deng, Xiaocui; Wang, Yudan; Tian, Lei; Yang, Meilian; He, Shuyue; Liu, Yaping; Khan, Afsar; Li, Yanping; Cao, Jianxin; Cheng, Guiguang
Abstract: Ethnopharmacological relevance: Anneslea fragrans Wall. is traditionally used as a folk medicine in treating indigestion, fever, dysentery, diarrhea, and liver inflammation in China, Vietnam and Cambodia. However, its anti-inflammatory activity and mechanism under a safety therapeutic dose as well as the main chemical components have not yet been fully investigated. Aim of the study : This study aimed to explore the therapeutic effect and possible molecular mechanisms of aqueous-methanol extract (AFE) of A. fragrans leaves on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) mice and illustrate its potent anti-inflammatory chemical compounds. Materials and methods: The AFE was obtained and then analyzed by high performance liquid chromatography (HPLC). Phytochemical investigation on the AFE was carried out to isolate and characterize its major components. The acute toxicity test was performed to provide the safety information of AFE. Subsequently, the protective effect of AFE on DSS-induced UC was evaluated by physiological changes, histopathological and immunohistochemical analysis, and the expressions of antioxidant enzyme, pro-inflammatory cytokines and anti-inflammatory cytokines. The expressions of target proteins in nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) were determined by western blot analysis. The tight junction (TJ) proteins in colon tissue were performed by immunohistochemical technique for evaluating the intestinal barrier integrity. Results: HPLC guided isolation of AFE resulted into two dihydrochalcones, which were elucidated as vacciniifolin (1 ) and confusoside (2 ). Acute toxicity evaluation revealed that median lethal dose (LD50 ) of AFE was greater than 5000 mg/kg. Furthermore, AFE significantly attenuated ulcerative colitis symptoms, suppressed myeloperoxidase activity, and increased the expression of superoxide dismutase and glutathione. AFE treatment could also reduce the levels of tumor necrosis factor- α, interleukin-1 β, and interleukin-6 and increase the levels of interleukin-4 and interleukin-10 in colon tissues and serum of DSS-induced UC mice. In addition, AFE significantly increased the expression of zonula occludens-1, occludin and claudin-1, and inhibited the phosphorylation of target protein of the NF-κB and MAPK signaling pathways in colon tissue. Conclusion: Dihydrochalcone glycosides are the major chemical constituents in AFE. AFE ameliorated DSS-induced UC in mice by inhibiting the inflammatory response via modulation of NF-κB and MAPK pathways and maintaining the intestinal barrier function, indicating that the plant A. fragrans could be used as a therapeutic candidate for ulcerative colitis. Graphical abstract: Image 1